Minimally Invasive Spine Surgery: The Learning Curve of a Single Surgeon. Issue 8 (December 2020) - Kimchi, Gil; Orlev, Alon; Hadanny, Amir; Knoller, Nachshon; Harel, Ran
Study Design: Retrospective cohort study. Objectives: The learning curve associated with the implementation of minimally invasive spinal surgery (MIS) has been the center of attention in numerous publications. So far, these studies referred to a single MIS procedure. In our view, minimally invasive surgical skills are acquired simultaneously through a variety of procedures that share common features. The aim of this study was to analyze the skills progression of a single surgeon implementing diverse minimally invasive techniques. Methods: We retrospectively collected all patients who underwent spinal surgery for thoracic or lumbar pathology by a single surgeon between 2012 and 2015 at a single institute. Both minimally invasive as well as open surgical techniques were analyzed; these groups were compared on the basis of surgical indications and outcomes. Skills progression analysis in reference to minimally invasive technique was performed. Results: A total of 230 patients met the inclusion criteria for this study. MIS group included higher percentage of lumbar discectomy and the open-surgery group included higher percentage of tumor resection surgery. Learning curve evaluation demonstrated increased surgical complexity, evaluated by number of levels treated, over the 4-year period, which corresponded with decreased complication rates. Discussion: A gradual increase in surgical complexity over 4 years, together with careful patient selection, enables the surgeon to maintain the rate of complication within acceptable limits. The main challenge facing the MIS community is constructing an education program for MIS surgeons in order to reduce the learning curve–induced complications. Conclusion: Advancement of educational aids for MIS surgical skill improvement, including spine models, virtual and augmented reality aids and surgical simulators may reduce the learning curve of spine surgeons.